2019
DOI: 10.1039/c9ce00867e
|View full text |Cite
|
Sign up to set email alerts
|

The structural evolution and tunable photoluminescence of f-element bearing coordination polymers of the 2,4,6-tri-α-pyridyl-1,3,5-triazine ligand

Abstract: An attempt at expanding the family of f-element bearing TPTZ coordination polymers has resulted in fifteen new complexes with topologies that evolved along the periodic table and tunable photoluminescence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…They reported the synthesis and fluorescence investigations of three different phases of lanthanide complexes 125-127 (first phase include: Ln = Pr to Nd; second phase: Ln = Pr to Er, except Pm; and the last phase include Ln = Tm to Lu) via solvothermal synthesis and also the novel uranyl TPTZ complex 128 (Scheme 51). [116] The photoluminescence results showed that the homoleptic Eu(III), Tb(III), and U(III) exhibited luminescence and when Eu(III) doped Tb(III) in a single complex giving rise a versatile photoluminescent color.…”
Section: Pt-tptz Complexesmentioning
confidence: 98%
See 1 more Smart Citation
“…They reported the synthesis and fluorescence investigations of three different phases of lanthanide complexes 125-127 (first phase include: Ln = Pr to Nd; second phase: Ln = Pr to Er, except Pm; and the last phase include Ln = Tm to Lu) via solvothermal synthesis and also the novel uranyl TPTZ complex 128 (Scheme 51). [116] The photoluminescence results showed that the homoleptic Eu(III), Tb(III), and U(III) exhibited luminescence and when Eu(III) doped Tb(III) in a single complex giving rise a versatile photoluminescent color.…”
Section: Pt-tptz Complexesmentioning
confidence: 98%
“…[115] The exploration of the f-elements with the imine chelators (N-donor ligands) have experienced increasing attention due to remarkable applications in different fields such as catalysis, magnetism, separation, and photoluminescence. Notable success have been witnessed by Yue et al, in 2019. They reported the synthesis and fluorescence investigations of three different phases of lanthanide complexes 125-127 (first phase include: Ln = Pr to Nd; second phase: Ln = Pr to Er, except Pm; and the last phase include Ln = Tm to Lu) via solvothermal synthesis and also the novel uranyl TPTZ complex 128 (Scheme 51).…”
Section: Pt-tptz Complexesmentioning
confidence: 99%
“…The tptz molecule was extensively exploited as a ligand for lanthanide or transition metal ions due to its various coordinating modes acting as a monoor bis-tridentate or/and bidentate ligand. [37][38][39][40][41] These d/f frameworks, with different topologies, showed interesting magnetic, chiral and luminescence properties. [37][38][39][40][41] Moreover, complex cations with tptz and {M(tptz)} n+ were also used as building blocks to assemble, in combination with cyanido-based metalloligands, cyanido-bridged d-d′ or d-f heterometallic complexes, such as [Mn II (tptz)(H 2 O)(NO 3 )(µ-NC)Cr III (ampy)…”
Section: Introductionmentioning
confidence: 99%
“…This effect, called “lanthanide contraction”, has been well studied and documented [ 5 , 6 , 7 , 8 , 9 ]. A variety of ligands have been shown to form complexes with lanthanides and the importance of lanthanide contraction on the structure of the formed complexes has been demonstrated [ 10 , 11 , 12 ]. Recently, we observed the effect of lanthanide contraction on tetrabutyl 1,10-phenanthroline-2,9-diamide [ 13 ], which acts as an N,N,O,O-tetradentate ligand.…”
Section: Introductionmentioning
confidence: 99%